2023
DOI: 10.3390/gels9070539
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera-Based Hydrogels for Wound Healing: Properties and Therapeutic Effects

Abstract: Aloe vera-based hydrogels have emerged as promising platforms for the delivery of therapeutic agents in wound dressings due to their biocompatibility and unique wound-healing properties. The present study provides a comprehensive overview of recent advances in the application of Aloe vera-based hydrogels for wound healing. The synthesis methods, structural characteristics, and properties of Aloe vera-based hydrogels are discussed. Mechanisms of therapeutic agents released from Aloe vera-based hydrogels, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 188 publications
1
16
0
Order By: Relevance
“…[ 23 ] After wound formation, inflammation mediates the balance between wound healing and fibrosis. [ 29 ] The use of anti-inflammatory agents aids in wound healing but also negatively affects cells that prevent fibrosis development. Fibroblasts and myofibroblasts play a crucial role in the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] After wound formation, inflammation mediates the balance between wound healing and fibrosis. [ 29 ] The use of anti-inflammatory agents aids in wound healing but also negatively affects cells that prevent fibrosis development. Fibroblasts and myofibroblasts play a crucial role in the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts and myofibroblasts play a crucial role in the development of fibrosis. [ 29 ] In one study, local application of AV was reported to result in prolonged retention of proinflammatory agents such as vascular endothelial growth factor (VEGF) in the tissue and a higher fibroblast density. [ 27 ] This study supports the results of local AV application for fibrosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This unique characteristic endows hydrogels with a sponge-like quality, allowing them to absorb and retain large amounts of water while retaining their shape and mechanical properties. Hydrogels can be synthesized from both natural and synthetic polymers, offering a wide range of options for tailoring their properties to suit specific applications [33,34].…”
Section: Hydrogelsmentioning
confidence: 99%
“…Aloe vera (AV) belongs to the Liliaceae family, of which the best-known species is Aloe Barbadensis Miller [ 86 ]. Aloe vera extract helps to improve oral bioavailability and acts as a good bio-enhancer [ 87 ].…”
Section: Herbal Bioactives Loaded Nanoformulations For Oral Deliverymentioning
confidence: 99%